((7y+9)/6)+((y-6)/3)=4

Simple and best practice solution for ((7y+9)/6)+((y-6)/3)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((7y+9)/6)+((y-6)/3)=4 equation:


y in (-oo:+oo)

(7*y+9)/6+(y-6)/3 = 4 // - 4

(7*y+9)/6+(y-6)/3-4 = 0

(3*(7*y+9))/(3*6)+(6*(y-6))/(3*6)+(-4*3*6)/(3*6) = 0

3*(7*y+9)+6*(y-6)-4*3*6 = 0

27*y-72-9 = 0

27*y-81 = 0

(27*y-81)/(3*6) = 0

(27*y-81)/(3*6) = 0 // * 3*6

27*y-81 = 0

27*y-81 = 0 // + 81

27*y = 81 // : 27

y = 81/27

y = 3

y = 3

See similar equations:

| 5x^(2/3)-44x^(1/3)-9 | | h-0.78=2.65 | | (4u-3)/5=4-((7u-2)/4) | | 4x+2x-x+3x= | | (7-3)2+3(8)= | | (4f+13g)(2w)= | | 7/2x-5=4/x+1 | | (4v-4)/3=((v+1)/6)+2 | | =x^2+22x+72 | | 11+21(11)=(13+c)13 | | 12y-10=-11+9y | | 3(x-6)/4=4x+6 | | 3(2n+1)+4(n-2)= | | h/2+7=10 | | 1=n/4-1 | | 20=5x+7x^2 | | 14=9-p | | 2+x/5=0 | | 4+b/-2=-2 | | 0=14d+8d^2 | | (6+y)(2y+5)=0 | | 12x+15=5x+62 | | 5x+x-4=-4 | | 2/3x-1/2y=12 | | (6x-4)-(2x+5)= | | 2/10=b/5 | | Y-12X+4Y+16=0 | | (13a+9b)-(2a-4b)= | | -2(w+4)=2w-24 | | 4y+3=-21 | | 72=9y+36 | | 4(-x-2)+3=15 |

Equations solver categories